2009
DOI: 10.1002/art.24625
|View full text |Cite
|
Sign up to set email alerts
|

Role of osteopontin in induction of monocyte chemoattractant protein 1 and macrophage inflammatory protein 1β through the NF‐κB and MAPK pathways in rheumatoid arthritis

Abstract: Objective. Osteopontin (OPN) is a proinflammatory protein with a critical role in leukocyte migration. Although OPN has been implicated in rheumatoid arthritis (RA), its underlying mechanism remains unknown. In this study, we investigated the role and molecular mechanism of OPN in the induction of 2 key chemokines, monocyte chemoattractant protein 1 (MCP-1) and macrophage inflammatory protein 1␤ (MIP-1␤), in RA.Methods. Enzyme-linked immunosorbent assay and quantitative polymerase chain reaction were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 41 publications
2
64
0
2
Order By: Relevance
“…27,28 It has been reported that OPN regulates MCP-1 expression through the NF-kappaB and MAPK pathways in rheumatoid arthritis. 29 Furthermore, the fact that there is no difference in the ability of the three OPN transcripts to regulate MCP-1 and TGF-b1 suggests that OPN transcripts may regulate both cytokines through the common receptor binding domain. The data that OPN transcripts regulate MCP-1 via CD44 (a common receptor present in all OPN transcripts) further support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 It has been reported that OPN regulates MCP-1 expression through the NF-kappaB and MAPK pathways in rheumatoid arthritis. 29 Furthermore, the fact that there is no difference in the ability of the three OPN transcripts to regulate MCP-1 and TGF-b1 suggests that OPN transcripts may regulate both cytokines through the common receptor binding domain. The data that OPN transcripts regulate MCP-1 via CD44 (a common receptor present in all OPN transcripts) further support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Osteopontin (also known as secreted phosphoprotein 1, SPP1), an adhesive glycophosphoprotein widely expressed in tissues, body fluids, and cells under normal conditions, regulates physiologic processes such as development, differentiation, inflammation, and wound healing. [6][7][8][9] In addition, SPP1 is highly expressed in the microenvironment of various tumors, both by malignant and host cells. [10][11][12] Osteopontin has been linked with enhanced tumor progression and metastasis by modulating cell-cell interactions, by activating signal transduction pathways, by altering gene expression, and by promoting tumor cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…OPN is an important mediator of the immune response as it is involved in cell migration and Th1-mediated immunity (7,8). OPN was found to selectively induce expression of proinflammatory chemokines and acted as a crucial mediator in the rheumatoid synovium (9,10). Accumulating evidence suggests that higher OPN levels could be observed in the synovial fluid and synovial membrane in RA patients (11,12).…”
mentioning
confidence: 99%